Peculiarities of Credit Risk Management in Credit Unions - Freitakas, E.; Rimsiene, V. (Економічний вісник Донбасу, 2010)
This artical examines credit risk management with the view based on theoretical and practical aspects in credit unions. The analysis of the scientifical references and empirical investigations showed that quality of the credit portfolio and the level of the delinquent loans depend on economical, legal and social environment as well as the credit union prudence in lending activities and loan allocating process. Fuzzy goal programming techniques can be efficiently applied in developing sophisticated investment decision making models to provide feasible solutions for credit union portfolio management and credit risk problems. Key words: credin union, credit risk management, fuzzy goal programming. У статті досліджено теоретичні й практичні аспекти управління кредитним ризиком в кредитних спілках. На основі теоретичних і практичних досліджень обґрунтовано, що якість кредитного портфелю і кількість прострочених кредитів залежать і від економічного, юридичного та соціального середовища, і від обережності та обачності кредитної спілки у процесі надання кредитів. Методи fuzzy goal програмування можуть бути успішно використані при створенні складних моделей управління портфелем кредитів і вирішенні проблем управління кредитними ризиками в кредитних спілках. Ключові слова: кредитна спілка, управління кредитним ризиком, fuzzy goal програмування. В статье исследуются теоретические и практические аспекты управления кредитным риском в кредитных союзах. На основе теоретических и практических исследований обосновывается, что качество кредитного портфеля и количество просроченных кредитов зависят как от экономической, юридической и социальной среды, так и осторожности и осмотрительности кредитного союза в процессе предоставления кредитов. Методы fuzzy goal програмирования могут быть успешно использованы в создании сложных моделей управления портфелем кредитов и решении проблем управления кредитными рисками в кредитных союзах. Ключевые слова: кредитный союз, управление кредитным риском, fuzzy goal програмирование.